Impact of HIV-Status Disclosure on Adherence to Antiretroviral Therapy Among HIV-Infected Children in Resource-Limited Settings: A Systematic Review. - Nichols, Justin; Steinmetz, Alexis; Paintsil, Elijah (AIDS and behavior, 2016)
Pediatric HIV remains a significant global health dilemma, especially in resource-constrained nations. As access to ART increases around the world, areas of concern in pediatric HIV treatment include age-appropriate disclosure of HIV status to children and development of adherence habits over time. This review was conducted to synthesize quantitative associations reported between disclosure and adherence among children living with HIV in resource-limited settings. An electronic database search of PubMed, MEDLINE and Cochrane returned 1348 results after removal of duplicates, 14 of which were found to meet inclusion criteria. Review of these reports showed conflicting results regarding the impact of disclosure on adherence, with 5 showing no association, 4 showing a negative impact of disclosure on adherence, and 5 showing positive benefits of disclosure for adherence habits. Thus, there was no clear consensus on the effect, if any, that disclosure has on medication adherence. Longitudinal, prospective research needs to be conducted to evaluate further impacts that disclosure may have on adherence habits over time, and interventions must be structured to link the two processes together in order to maximize health benefit to the child or adolescent.